Students’ Satisfaction of Food Services at the University Cafeteria: a Comparative Study Via PLS Approach - Mui -Ling Chang, Dyana; Mohd Suki, Norazah (International Journal of Engineering and Technology, 2018)
This research investigated the effect of food quality, price fairness, staff performance, and ambience on students’ satisfaction of cafeteria food services by comparing responses from Universiti Malaysia Sabah (UMS), Malaysia with Mercu Buana University (MBU), Indonesia. Data was analysed using the Partial Least Squares (PLS) application in SmartPLS computer software version 2.0. Path coefficients from PLS results revealed ambience as the most significant predictor of students’ satisfaction of food services at the university cafeteria in both UMS and MBU settings, followed by aspects of staff performance and food quality. It is imperative for university cafeteria operators at both sites to uplift students’ satisfaction of food services at their cafeterias by enhancing ambiance such as installing decorations that project a warm and cosy environment. The result of these findings could be utilised as guidelines for the respective university management to incorporate elements that could improve food services in their cafeterias thus increasing the satisfaction of their users (students).